New Insights into Structural Evolution of LiNiO2 Revealed by Operando Neutron Diffraction. Issue 11 (8th September 2021) - Chien, Po‐Hsiu; Wu, Xianyang; Song, Bohang; Yang, Zhijie; Waters, Crystal K.; Everett, Michelle S.; Lin, Feng; Du, Zhijia; Liu, Jue
Abstract: LiNiO2 (LNO) represents the end member in the compositional space of the LiNi1‐ x‐y Mn x Coy O2 (as x and y approach zero) cathode system. Despite its high theoretical specific capacity (275 mAh/g), LNO suffers from phase transitions with large volume change and unfavorable reactions upon electrochemical cycling, which restricts its practical use in the application of lithium‐ion batteries. While the contributing factor to the structural instability is commonly linked to the undesired volume collapse associated with the H2‐H3 phase transition, detailed analysis of structural evolution following the entire route of phase transitions (H1‐M‐H2‐H3) in real time under battery operating conditions remains a challenging task. In this work, we employ operando neutron diffraction to study the structural changes (crystal lattice, Li/Ni−O bond length, O−Ni−O bond angles, and LiO2 /NiO2 layer thickness) of LNO cathode in a home‐built Li x NiO2 ||graphite full cell during Li + de‐/intercalation. In particular, the anomalous increase(decrease) of Ni−O(Li−O) bond length at high SOC (>∼85 %) in the H3 phase is discussed in the context of O 2− (2p)→Ni 4+ (3d) negative charge transfer. Abstract : Real time phase transition of electrode : Operando neutron diffraction was employed to track the phase transitions of LiNiO2 cathode and graphite anode during charging/discharging at C/10 for the first cycle in real time. Anomalous Li/Ni−O bond lengths in the H3 phase (LiNiO2 ) were identified and rationalized by the effect of negative charge transfer through Ni 4+ (3d)−O 2− (2p) rehybridization.